Insights into enhanced electrochemiluminescence of a multiresonance thermally activated delayed fluorescence molecule. Issue 2 (14th September 2022) - Yang, Liuqing; Dong, Lihui; Hall, David; Hesari, Mahdi; Olivier, Yoann; Zysman‐Colman, Eli; Ding, Zhifeng
Abstract: The electrochemiluminescence (ECL) behavior of a multiresonance thermally activated delayed fluorescence molecule has been investigated for the first time by means of ECL‐voltage curves, newly designed ECL‐time observatory, and ECL spectroscopy. The compound, Mes 3 DiKTa, shows complex ECL behavior, including a delayed onset time of 5 ms for ECL generation in both the annihilation pathway and the coreactant route, which we attribute to organic long‐persistent ECL (OLECL). Triplet‐triplet annihilation, thermally activated delayed fluorescence and uncompensated solution resistance cannot be ruled out as contributing mechanisms to the ECL. A very long ECL emission decay was attributed to OLECL as well. The absolute ECL efficiencies of Mes 3 DiKTa were enhanced and reached 0.0013% in annihilation route and 1.1% for the coreactant system, which are superior to those of most other organic ECL materials. It is plausible that ECL materials with comparable behavior as Mes 3 DiKTa are desirable in applications such as ECL sensing, imaging, and light‐emitting devices. Abstract : Newly designed time‐resolved electrochemiluminescence (ECL) experiments were employed to demonstrate unusual delayed ECL onset and long ECL decay of an multiresonance thermally activated delayed fluorescence (TADF) molecule, which arise from the contribution of organic long‐persistent ECL (OLECL). ECL spectroscopy provides evidence of a combination of monomer and aggregates emissions. The TADF and OLECL lead to an emission enhancement with superior ECL efficiency.